Penggunaan Media Wordwall (Cari Kata Sejarah) Untuk Meningkatkan Motivasi Belajar Siswa Materi Pengaruh Hindhu Buddha di Indonesia Kelas X-A SMAN 5 Madiun - Arsitha, Elsa Devi; Hartono, Yudi; Nurkhilipah, Siti (LPPM Universitas Putera Batam, 2024)
This study aims to improve students' learning motivation by using Wordwall media (Search for Historical Words). Wordwall media is an interactive learning media based on technology that can be easily accessed. This type of research is Classroom Action Research (CAR) initiated by Kemmis & McTaggart. This research was conducted at SMAN 5 Madiun with 34 students as subjects of class X-A. The data collection method used in this study was a test and observation conducted directly by the researcher. The analysis technique used is descriptive quantitative and qualitative. The use of these techniques describes in detail the implementation of learning with Wordwall Media (Search for Historical Words), the Culturally Responsive Teaching (CRT) approach, and the Problem Based Learning (PBL) Model.